What America's Users Spend on Illegal Drugs, 2000–2010 - B. Kilmer, S. Everingham (RAND Corporation, 2014)
A sense of scale is a prerequisite to thinking sensibly about illicit drug markets. For example, knowing whether a country consumes tens, hundreds, or thousands of metric tons (MTs) of a prohibited substance is critical for understanding the impact of a three-MT seizure at a border crossing. But decisionmakers need more than a sense of scale; they also need figures with enough precision to be able to determine whether the markets have become larger or smaller over time. In January 2012, the U.S. White House Office of National Drug Control Policy (ONDCP) asked RAND to generate national estimates of the total number of users, total expenditures, and total consumption for four illicit drugs from 2000 to 2010: cocaine (including crack), heroin, marijuana, and methamphetamine (or meth). This report explains our methodology and presents our results.